Dynamic substructures, volume 4 : proceedings of the 38th IMAC, A Conference and Exposition on Structural Dynamics 2020.: proceedings of the 38th IMAC, A Conference and Exposition on Structural Dynamics 2020. Volume 4 ([2021]) - Unknown
No abstract available